"I6 passages: on the reproduction of a human embryonic stem cell line from Israel to France". Issue 4 (2nd October 2018) - Merleau-Ponty, Noémie; Vertommen, Sigrid; Pucéat, Michel
Abstract : The first French clinical trial using human embryonic stem cells for regenerative purposes was launched in 2014, using the I6 stem cell line that was imported from Israel. From Israel to France, national reproductive policies and practices inform how basic scientists produce, manage and circulate cells across countries. Building on an interdisciplinary co-production involving two social scientists and a life scientist, this article suggests that biobanks passage cells from in vitro fertilization to stem cell science and from country to country by modifying their reproductive meaning. Four passages are described: the absence of cells in 2005 when the research started in France; the presence of supernumerary embryos available for research in Israeli IVF biobanks; the production of the I6 stem cell bank in Israel; the importation and laboratory biobanking of the cells in France. Human embryonic stem cell lines can never be completely disentangled from reproduction.